2015
DOI: 10.1063/1.4936773
|View full text |Cite
|
Sign up to set email alerts
|

Some studies on generalized coordinate sets for polyatomic molecules

Abstract: Generalized coordinates are widely used in various analyses of the trajectories of polyatomic molecules from molecular dynamics simulations, such as normal mode analysis and force distribution analysis. Here, we presented detailed discussions on the properties of some specific sets of generalized coordinates, which separate translational, rotational, and vibrational motions of a molecule from one another once the trajectories of dynamical systems are known. Efficient methods were suggested for estimating the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…45 In the computation of energy flow quantities, exact separation between internal and external DOFs was achieved by proper choice of external coordinates, as detailed in a recent publication. 46…”
Section: A Methodsmentioning
confidence: 99%
“…45 In the computation of energy flow quantities, exact separation between internal and external DOFs was achieved by proper choice of external coordinates, as detailed in a recent publication. 46…”
Section: A Methodsmentioning
confidence: 99%
“…As shown in a recent paper, 48 this coordinate set can separate the six external movements from the internal ones. The internal coordinates consist of the bonds, angles, and dihedral angles (the BAT coordinates).…”
Section: B Decomposition Of the Potential Energymentioning
confidence: 99%
“…Therefore, the coordinate set we chose according to Ref. 48 is of minimum dependence between the potential energy on each coordinate and should be the preferred choice. More detailed explanations are presented in the supplementary material.…”
Section: B a Committor-free Procedures For Identifying Relevant Coordmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that a complete set of coordinates can be constructed to separate the translational, rotational, and vibrational movements of the system . Thus, the translational, rotational, and vibrational components of EAWs can be obtained by the summation of EAWs on the corresponding coordinates.…”
Section: Methodsmentioning
confidence: 99%